Residuation Properties and Weakly Primary Elements in Lattice Modules. (26th November 2014) - Manjarekar, C. S.; Kandale, U. N.
Abstract : We obtain some elementary residuation properties in lattice modules and obtain a relation between a weakly primary element in a lattice module M and weakly prime element of a multiplicative lattice L .